MRI-Based Optimization Design of the Pre-Spinal Route of Contralateral C7 Nerve Transfer for Spastic Arm Paralysis - Zhao, Hua-Li; Gao, Yun; Yu, Ai-Ping; Wei, Yi-Min; Shen, Yun-Dong; Jiang, Su; Qiu, Yan-Qun; Yu, Jing; Liang, Zong-Hui (Frontiers in Surgery, 2022)
Purpose The pre-spinal route of contralateral cervical 7 nerve transfer developed by Prof. Wendong Xu helps realize the direct anastomosis of the bilateral cervical 7 nerves. However, there are still no less than 20% operations requiring nerve graft, which leads to unfavorable prognosis. This study aimed to explore the optimized pre-spinal route with MRI to further improve the prognosis. Methods The current study enrolled 30 patients with the central spastic paralysis of upper limb, who underwent contralateral cervical 7 nerve transfer via Prof. Xu's pre-spinal route through the anterior edge of the contralateral longus colli. MR images were used to analyze the route length, vertebral artery exposure and contralateral cervical 7 nerve included angle. Three pre-spinal routes were virtually designed and analyzed. The selected optimal route was applied to another 50 patients for contralateral cervical 7 nerve transfer. Results As indicated by the 30 patients, the middle route and the posterior route were shorter than the anterior route in length, but with no statistical difference between the two routes. Of 30 contralateral vertebral arteries, 26 were located at the posterior medial edge of the longus colli. The average included angle of the anterior, middle and posterior route was 108.02±7.89°, 95.51±6.52°, 72.48±4.65°, respectively. According to these data, the middle route was optimally applied to 50 patients, where the rate of nerve transplantation was only 4%, and no such serious complications as vertebral artery and brachial plexus injury occurred. Conclusion According to the 50 patients' low rate of nerve transplantation and their absence of serious complications, the middle route was the optimal.